Mass spectrometry based lipid(ome) analyzer and molecular platform: a new software to interpret and analyze electrospray and/or matrix‐assisted laser desorption/ionization mass spectrometric data of lipids: a case study from Mycobacterium tuberculosis. (26th March 2013) - Sabareesh, Varatharajan; Singh, Gurpreet
Abstract : Mass Spectrometry based Lipid(ome) Analyzer and Molecular Platform (MS‐LAMP) is a new software capable of aiding in interpreting electrospray ionization (ESI) and/or matrix‐assisted laser desorption/ionization (MALDI) mass spectrometric data of lipids. The graphical user interface (GUI) of this standalone programme is built using Perl::Tk. Two databases have been developed and constituted within MS‐LAMP, on the basis of Mycobacterium tuberculosis ( M .  tb ) lipid database (www.mrl.colostate.edu) and that of Lipid Metabolites and Pathways Strategy Consortium (LIPID MAPS; www.lipidmaps.org). Different types of queries entered through GUI would interrogate with a chosen database. The queries can be molecular mass(es) or mass‐to‐charge ( m / z ) value(s) and molecular formula.L IPIDM APS identifier also can be used to search but not for M .  tb lipids. Multiple choices have been provided to select diverse ion types and lipids. Satisfying to input parameters, a glimpse of various lipid categories and their population distribution can be viewed in the output. Additionally, molecular structures of lipids in the output can be seen using ChemSketch (www.acdlabs.com), which has been linked to the programme. Furthermore, a version of MS‐LAMP for use in Linux operating system is separately available, wherein PyMOL can be used to view molecular structures that result as output from General Lipidome MS‐LAMP. The utility of this software is demonstrated using ESI mass spectrometric data of lipid extracts of M .  tb grown under two different pH (5.5 and 7.0) conditions. Copyright © 2013 John Wiley & Sons, Ltd.